Langston Hughes chez Pierre Seghers : récit d’un engagement poétique - Annick Ettlin (Transatlantica)
Although the Harlem Renaissance considerably influenced the poets of the “negritude” movement, its editorial and academic reception among French writers and readers has been quite confidential. Yet between the translation of several poems in the 1920s and a growing number of studies produced by French researchers since 2000, the poetry of Langston Hughes in particular has been channeled towards French readers, in the 1950s and 1960s, mainly through the journal Présence Africaine and, more surprisingly, the publishing house of Pierre Seghers. This article seeks to describe the promotion of Hughes’s work by Seghers between 1947 and 1966. It examines the choices and circumstances leading to the publication of several of Hughes’s works: his first autobiography, a volume of poetry (translated by François Dodat in 1955), a book in the series “Poètes d’aujourd’hui” and two anthologies in 1962 and 1966. It also relies on the correspondence between Hughes and Seghers from 1955 to 1966 (which is kept in the Beinecke Library at Yale University). The study of this corpus of texts leads me to the following hypothesis: Langston Hughes’s reception in France was determined by the interventions of Seghers, who, rather than emphasize his status as one of the leaders of the Harlem Renaissance or as a political author, highlighted his commitment to the democratic diffusion of his poetry. In Seghers’s view, his biography and his work can be seen as a model poetic gesture: both active and likely to solicit action.